Cooperative dynamic non-zero-sum of two-person game - Vakrinienė, S. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:С. Вакринене. Кооперативная динамическая неантагонистическая игра двух лицS. Vakrinienė. Kooperatinis dinaminis neantagonistinis dviejų asmenų lošimas